2000
DOI: 10.1063/1.480975
|View full text |Cite
|
Sign up to set email alerts
|

Near edge X-ray absorption fine structure measurements (XANES) and extended x-ray absorption fine structure measurements (EXAFS) of the valence state and coordination of antimony in doped nanocrystalline SnO2

Abstract: Colloids of nanocrystalline tin dioxide containing 9.1 at. % and 16.7 at. % antimony have been prepared by the coprecipitation method. High-resolution transmission electron microscopy (TEM) images show crystalline particles in the 2–6 nm size regime. X-ray powder diffraction patterns of nanocrystalline powders obtained by drying the colloids and heating to 100 °C indicate the same rutile lattice structure known from bulk SnO2. On heating to 500 °C in air, the nanocrystalline powder shows a slight increase in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
146
4
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(170 citation statements)
references
References 53 publications
14
146
4
6
Order By: Relevance
“…In the case of higher concentration of antimony embeded in the SnO 2 lattice the most likely the resulted solid solution has the the following composition: Sn 4+ 1-2x Sb 3+ x Sb 5+ x O 2-2 . By EXAFS it has been established that Sb dopants occupy Sn sites in the rutile structure [Chadwick et al,1993;Rockenberger et al, 2000]. XANES measurements showed that the largest fraction of Sb has a valency of 5 + , although 3 + was also observed in nanocrystalline SnO 2 .…”
Section: Sno 2 -Sb 2 O 3 Binary Systemmentioning
confidence: 99%
“…In the case of higher concentration of antimony embeded in the SnO 2 lattice the most likely the resulted solid solution has the the following composition: Sn 4+ 1-2x Sb 3+ x Sb 5+ x O 2-2 . By EXAFS it has been established that Sb dopants occupy Sn sites in the rutile structure [Chadwick et al,1993;Rockenberger et al, 2000]. XANES measurements showed that the largest fraction of Sb has a valency of 5 + , although 3 + was also observed in nanocrystalline SnO 2 .…”
Section: Sno 2 -Sb 2 O 3 Binary Systemmentioning
confidence: 99%
“…A combinação das transições de RE com semicondutores de gap largo, como é o caso do SnO 2 (3,6 eV) [2] leva a uma alta efi ciência na emissão [3,4]. Além disso, SnO 2 apresenta alta refl etividade no infravermelho, transparência de cerca de 90% no visível [5,6], e boa condutividade elétrica, propriedades que tornam este material adequado para várias aplicações tecnológicas, incluindo sensores de gás, células solares, entre outras [6,7]. O íon Ce 3+ apresenta confi guração eletrônica 4f 1 no estado fundamental e 5d 1 no estado excitado.…”
Section: Introductionunclassified
“…A combinação das transições de RE com semicondutores de gap largo, como é o caso do SnO 2 (3,6 eV) [2] leva a uma alta eficiência na emissão [3,4]. Além disso, SnO 2 apresenta alta refletividade no infravermelho, transparência de cerca de 90% no visível [5,6], e boa condutividade elétrica, propriedades que tornam este material adequado para várias aplicações tecnológicas, incluindo sensores de gás, células solares, entre outras [6,7]. O íon Ce 3+ apresenta configuração eletrônica 4f 1 no estado fundamental e 5d 1 no estado excitado.…”
Section: Introductionunclassified